Genetics and Genomics of Pulmonary Arterial Hypertension - Southgate, Laura; Machado, Rajiv (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Pulmonary arterial hypertension is a severe and progressive disorder affecting the blood vessels in the lungs. Typically, symptoms first appear at around 30-40 years of age and, without treatment, can lead to fatal heart disease within a few years. Genetic studies over the past decade have identified numerous genes that contribute to disease progression but, for many sufferers, the underlying genetic cause remains elusive. The collection of reviews and original research articles contained within this book provide an overview of recent advancements in understanding the genetic risk factors for pulmonary arterial hypertension. We further examine the emerging interplay between genetic variants and clinical outcomes, providing a framework for new treatments and improved patient care.